Investigation of Triple Symmetric Non-halogen Benzene Derivative Solvent for Spray-Coated Polymer Solar Cells - Tang, Yang; Tang, Hua; Bai, Youjun; Hu, Rong; Yan, Xinwu; Li, Lu; Cheng, Jiang (Frontiers in Chemistry, 2021)
The performance of spray-coated polymer solar cells could be largely improved via morphologies and phase optimization by solvent engineering. However, there is still a lack of fundamental knowledge and know-how in controlling blend morphology by using various solvents. Here, the effect of adding low polar benzene and non-halogen benzene derivatives with triple symmetric molecular have been systematically investigated and discussed. It is found that the triple symmetric non-halogen benzene could promote the formation of preferential face-on molecule orientation for PBDB-T-2Cl:IT4F films by grazing incidence wide-angle X-ray scattering. The X-ray photoelectron spectroscopy shows that PBDB-T-2Cl could be transported to the surface of the blend film during drying process. 3D opt-digital microscope shows that triple symmetric non-halogen benzene could also improve the morphologies of active layers by reducing the coffee-ring or other micro-defects. Due to the appropriate vapour pressures, devices with mixing 20% benzene or the triple symmetric non-halogen in spray solution could significantly improve the device performance. Device prepared using 20% 1,3,5-Trimethylbenzene (TMB) and 80% chlorobenzene (CB) mixture solvent has the best morphology and phase structure, and the power conversion efficiency (PCE) of the device was increased nearly 60% to 10.21% compared with the device using CB as the only solvent.